A production process for simultaneously preparing multiple molecular weight gradient degradable materials
Through polycondensation, viscosity-enhancing and cracking-refining-polymerization processes, combined with twin-screw extruder, the problem of difficulty in preparing PGAs with different molecular weight gradients in the prior art is solved, and efficient production of multiple PGA products is achieved, reducing production costs , and expanded its application scope.
Patent Information
- Application Number
- CN202310141165.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-21
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-02-21
AI Technical Summary
The prior art is difficult to efficiently prepare degradable polyglycolic acid (PGA) materials with different molecular weight gradients at the same time, resulting in limited application and high production costs, which affects its promotion and application.
The two processes of polycondensation-adhesion-enhancing and cracking-purification-polymerization are adopted to achieve the preparation of medium and low molecular weight and high molecular weight PGA through prepolymerization, granulation and solid phase polymerization steps, and the production cost is reduced.
The simultaneous preparation of multiple molecular weight gradient PGAs is realized, which reduces the investment cost of production equipment, expands the application range of PGAs, and produces various types of PGA products through self-enhancement technology to meet different application needs.
Smart Images

Figure CN116284698B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material preparation, and in particular relates to a production process for simultaneously preparing degradable materials with multiple molecular weight gradients. Background Art
[0002] Degradable materials, with their reliable biosafety and good biodegradability, have occupied a considerable share of the plastic market. Their research and application have greatly reduced the difficulty of centralized treatment of plastic waste. Among them, polyglycolic acid (PGA), as a fully biodegradable material, has the advantages of mild degradation conditions, fast degradation speed and no need for special degradation conditions. It can achieve rapid degradation in the natural environment and eventually degrade into carbon dioxide and water. It is widely used in agricultural films and biomedical polymer industries.
[0003] However, the uses of PGA polymers with different molecular weights vary significantly.
[0004] Generally speaking, PGA with a molecular weight of more than 10,000 can be used as medical absorbable sutures, but its strength is not enough for fractures or other internal fixations. When the average molecular weight of PGA reaches 20,000 to 145,000, the polymer can be drawn into fibers, and the molecular arrangement of the polymer can be made directional, which also enhances the strength of PGA. Such PGA can be made into films or other different shapes. In addition, the mechanical strength of PGA after self-reinforcement is greatly improved, generally 1 to 3 times or more of the PGA matrix, and is more widely used.
[0005] Therefore, developing a production process that can simultaneously prepare PGA products with multiple molecular weight gradients and reduce the investment cost of PGA are of great significance for the promotion and application of degradable plastics. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a production process for simultaneously preparing a variety of molecular weight gradient degradable materials.
[0007] The production process provided by the present invention can simultaneously prepare a variety of molecular weight gradient degradable materials, which specifically includes the following four steps: (1) prepolymerization; (2) polycondensation-thickening, or cracking-purification-polymerization; (3) granulation; (4) solid phase polymerization.
[0008] The simultaneous preparation process of multiple molecular weight gradient degradable materials of the present invention is achieved through different polymerization processes in step (2); specifically, the two processes are a polycondensation-thickening process and a cracking-purification-polymerization process.
[0009] That is, the process of polycondensation-thickening is used to prepare medium and low molecular weight degradable materials; the process of cracking-refining-polymerization is used to prepare high molecular weight degradable materials;
[0010] Among them, the polycondensation in the preparation process of medium and low molecular weight biodegradable materials is direct polycondensation;
[0011] The polymerization in the preparation process of high molecular weight biodegradable materials is ring-opening polymerization.
[0012] The degradable material prepared by the present invention is specifically a high molecular polymer of alkyd.
[0013] The production granulation described in the above step (3) is achieved by using a twin-screw extruder.
[0014] The production process for simultaneously preparing a plurality of molecular weight gradient degradable materials in the present invention comprises the following four steps:
[0015] (1) Prepolymerization: weigh alkyd acid, dehydrating agent, and prepolymerization catalyst, add them into a reaction kettle, heat and stir, and keep the temperature for 1 to 3 hours when the temperature in the kettle rises to 120 to 140°C;
[0016] Wherein, the weight ratio of the prepolymerized catalyst to the raw material is 0.5%wt;
[0017] When the moisture content to be collected reaches 80% of the theoretical amount, the temperature in the kettle is raised to 150-170°C and maintained for 1-2 hours;
[0018] When the moisture content to be collected reaches 90% of the theoretical amount, vacuum operation is started and the pressure is gradually increased, the pressure is maintained at -20 to -90 KPa, and the temperature is adjusted to 160 to 180°C and maintained for 2 to 4 hours to obtain a prepolymer product;
[0019] (2) Polymerization: direct polycondensation to increase viscosity, or ring-opening polymerization to obtain polymer products;
[0020] (3) Production and granulation: The polymer intermediate prepared in step (2) is extruded and granulated using a twin-screw extruder to obtain pellets, with the screw speed set at 10 to 40 rpm and the extrusion temperature at 200 to 250° C.;
[0021] (4) Solid-phase polymerization: The pellets obtained in step (3) are subjected to solid-phase polymerization, wherein the pressure is maintained above -99 KPa and the temperature is 170° C. for 2 to 8 hours and 195° C. for 3 to 12 hours, respectively, to finally obtain alkyd polymer products with various molecular weight gradients.
[0022] In the above steps, step (2) of the process for preparing the medium and low molecular weight degradable material is carried out by a direct polycondensation process, which specifically comprises the following steps:
[0023] S1, polycondensation: transfer the prepolymer product obtained in step (1) to a polycondensation reactor, adjust the temperature to 180-200°C and the pressure to above -90KPa, add a condensation chain extender, and react for 1-2h to obtain a polycondensation product;
[0024] S2, viscosity increasing: the polycondensation product prepared in S1 is transferred to a viscosity increasing kettle at a temperature of 180-200°C and a pressure maintained above -95KPa to carry out a viscosity increasing reaction to obtain a polymer product.
[0025] In addition, step (2) of the process for preparing the high molecular weight biodegradable material is carried out by a ring-opening polymerization process, which specifically comprises the following steps:
[0026] S1, cracking: the prepolymer product obtained in step (1) is transferred to a cracking kettle, and a cracking catalyst and a cracking solution are added, the temperature is set to 200-250°C, the pressure is maintained above -95KPa, the reaction is further carried out for 6-12 hours, and the distillate is collected in a collection tank;
[0027] S2, refining: refining and purifying the crude polymer in the collection tank of step S1 to obtain a refined polymer product;
[0028] S3, polymerization: the refined polymer product obtained in step S2 is transferred to a polymerization device, and a polymerization catalyst is added, the temperature is set to 130-210° C., and the temperature is kept for 2-5 hours to obtain a polymer product.
[0029] Preferably, the dehydrating agent in step (1) is xylene, and the prepolymerization catalyst is nano zinc oxide.
[0030] Preferably, in step (2), the condensation chain extender of the direct polycondensation process is any one of 1,3-dicyclohexylcarbodiimide and ADR-4370S;
[0031] The cracking catalyst of the ring-opening polymerization process is any one of antimony trioxide, stannous octoate, and zinc acetylacetonate;
[0032] The cleavage solution is any one of a mixture of dioctyl terephthalate and polyethylene glycol 1000, a mixture of dioctyl terephthalate and polyethylene glycol monomethyl ether, and a mixture of butyl benzyl phthalate and polyethylene glycol 1000;
[0033] The polymerization catalyst is a mixed solution of stannous octoate and dodecanol.
[0034] In addition, the present invention also realizes the self-reinforced production of medium and low molecular weight PGA by high molecular weight PGA through a twin-screw extruder, and realizes the production of four types of products: glycolide, medium and low molecular weight PGA, high molecular weight PGA, and self-reinforced PGA.
[0035] The beneficial effects of the present invention are:
[0036] (1) The present invention proposes a mold trial production device and process that are compatible with two process routes, and can simultaneously prepare PGA products with multiple molecular weight gradients according to actual production needs;
[0037] (2) In the simultaneous preparation process of multiple molecular weight gradients provided by the present invention, the feed control system, high and low temperature control system, prepolymerization reaction device, production granulation device, solid phase polymerization device, etc. are all common equipment for each process, which greatly reduces the investment cost of process equipment and further reduces the production cost of PGA;
[0038] (3) The present invention also realizes the self-reinforced production of high molecular weight PGA on medium and low molecular weight PGA through extrusion granulation of a twin-screw extruder, thereby realizing the production of four types of products, namely, glycolide, medium and low molecular weight PGA, high molecular weight PGA, and self-reinforced PGA. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a production process diagram of various molecular weight gradient degradable materials of the present invention.
[0040] In the figure, there are a preheating tank 11, a prepolymerization kettle 12, a solvent reflux tank 13, a condensation kettle 21, a viscosity increasing kettle 22, a cracking kettle 31, a crude product collecting tank 32, a refining device 33, a ring-opening polymerization device 34, a twin-screw granulator 41, a granulator 42, a silo 43, a solid phase polymerization device 44, a heat exchanger 51, a condensate storage tank 52, a cyclone separation tank 53, a buffer tank 54, a vacuum pump 55, and a three-way switch valve 6. DETAILED DESCRIPTION
[0041] In order to enable those skilled in the art to better understand the present invention, the present invention is further described in conjunction with specific implementation methods.
[0042] Example 1
[0043] (1) Prepolymerization: Weigh the alkyd acid and dehydrating agent, add them into the prepolymerization reactor, set the heat transfer oil temperature at 130-140°C and the speed at 10-20 Hz, add the catalyst (0.5%wt of the raw material, made into a solution with the dehydrating agent), start heating and stirring, and keep the temperature in the reactor at 130°C for 2 hours;
[0044] When the collected moisture content reaches 80% of the theoretical amount, set the heat transfer oil temperature to 165°C, and maintain it for 1 to 2 hours after the temperature in the kettle rises to 160°C;
[0045] When the moisture content to be collected reaches 90% of the theoretical amount, vacuum operation is started and the pressure is gradually increased, the pressure is maintained at -20 to -90 KPa, and the temperature is adjusted to 160 to 180°C and maintained for 2 to 4 hours to obtain a prepolymer product;
[0046] (2) transferring the prepolymer product obtained in step (1) to a polycondensation reactor, adjusting the temperature to 180-200° C., maintaining the pressure above -90 KPa, adding a condensation agent, and further reacting for 1-2 hours to obtain a product;
[0047] Viscosity enhancement: the product prepared above is transferred to a viscosity enhancement kettle at a temperature of 180-200°C and a pressure maintained above -95KPa to obtain product 1;
[0048] (3) transferring product 1 to a twin-screw extruder, setting the screw speed to 10-40 rpm and the temperature to 200-250° C., and extruding and granulating the product using the twin-screw extruder;
[0049] (4) The pellets are transferred to a solid phase polymerization reaction device at a pressure of -99 KPa or above and at temperatures of 170°C for 2 to 8 h and 195°C for 3 to 12 h, respectively, to carry out solid phase polymerization to obtain product 11.
[0050] As attached Figure 1 In the production process diagram of various quality gradient degradable materials shown, the system structure used in the production process is as follows:
[0051] It includes prepolymerization device, polycondensation device, cracking device, refining device, ring-opening polymerization device, production granulation device, solid phase polymerization device, feed control system, high and low temperature control system, heat exchanger, condensate storage tank and vacuum device.
[0052] The system structure used in this production process is as follows:
[0053] It includes a prepolymerization device, wherein the outlet d of the prepolymerization device is respectively connected to the inlet a of the polycondensation device and the inlet a of the cracking device, and the outlet c of the prepolymerization device is connected to the inlet a of the heat exchanger 51; the outlet of the cracking device is connected to the inlet of the refining device 33, the outlet of the refining device 33 is connected to the inlet of the ring-opening polymerization device 34, the outlet of the ring-opening polymerization device 34 and the outlet of the polycondensation device are both connected to the inlet of the production granulation device; the outlet of the production granulation device is connected to the inlet of the solid-phase polymerization device 44; the outlet b of the heat exchanger 51 is connected to the inlet of the vacuum device, and the outlet c of the heat exchanger 51 is connected to the condensate storage tank 52.
[0054] The outlet channel d of the prepolymerization device leading to the polycondensation device and the cracking device is provided with a three-way switch valve 6, which is respectively connected to the inlet of the polycondensation device and the inlet of the cracking device.
[0055] The prepolymerization device includes a preheating tank 11, a prepolymerization kettle 12, and a solvent reflux tank 13; the inlet a of the preheating tank 11 is connected to the feed control system; the inlet b of the preheating tank 11 is connected to the inlet a of the prepolymerization kettle, and the inlet a and outlet b of the solvent reflux tank 13 are respectively connected to the outlet b and inlet c of the prepolymerization kettle 12 to form a reflux mode.
[0056] The cracking device includes a cracking kettle 31 and a crude product collection 32; the condensation device includes a condensation kettle 21 and a viscosity increasing kettle 22; the outlet c of the solvent reflux tank 13 in the cracking device is connected to the inlet of the heat exchanger 51; the outlet d of the prepolymerization kettle 12 is connected to the inlet a of the condensation kettle 21 and the inlet a of the cracking kettle 31 through a three-way switch valve 6.
[0057] The above system also includes a high and low temperature control system, which is respectively connected to the prepolymerization device, the polycondensation device and the cracking device.
[0058] The outlet b of the cracking kettle 31 is connected to the inlet of the heat exchanger 51 , the outlet c of the cracking kettle 31 is connected to the inlet of the crude product collecting tank 32 , and the outlet of the crude product collecting tank 32 is connected to the refining device 33 .
[0059] The outlet b of the polycondensation kettle 21 is connected to the inlet of the heat exchanger 51, the outlet c of the polycondensation kettle 21 is connected to the inlet of the viscosity increasing kettle 22, and the outlet of the viscosity increasing kettle 22 is connected to the inlet of the twin screw extruder 41; the twin screw extruder 41 is part of the production granulation device.
[0060] The production granulation device includes a twin-screw extruder 41, a granulator 42, and a silo 43. The inlet of the twin-screw extruder 41 is connected to the outlet of the viscosity increasing kettle 22 and the outlet of the open-loop polymerization device 34 respectively, the outlet of the twin-screw extruder 41 is connected to the inlet of the granulator 42, the outlet of the granulator 42 is connected to the inlet of the silo 43, and the outlet of the silo 43 is connected to the inlet of the solid-phase polymerization device 44.
[0061] The vacuum device includes a cyclone separation tank 53, a buffer tank 54, and a vacuum pump 55. The inlet of the cyclone separation tank 53 is connected to the outlet b of the heat exchanger 51, the outlet of the cyclone separation tank 53 is connected to the inlet of the buffer tank 54, and the outlet of the buffer tank 54 is connected to the inlet of the vacuum pump 55.
[0062] Example 2
[0063] (1) Weighing alkyd and dehydrating agent, adding them into a prepolymerization reactor, setting the heat transfer oil temperature to 130-140°C and the speed to 10-20 Hz, adding catalyst (0.5%wt of the raw material, made into a solution with dehydrating agent), starting heating and stirring, and maintaining the temperature in the reactor for 2 hours after it rises to 130°C;
[0064] When the moisture content of the collected water reaches 80% of the theoretical amount, set the temperature of the heat transfer oil to 165°C, and keep it warm for 1 to 2 hours after the temperature in the kettle rises to 160°C;
[0065] When the moisture content to be collected reaches 90% of the theoretical amount, vacuum operation is started and the pressure is gradually increased, the pressure is maintained at -20 to -90 KPa, and the temperature is adjusted to 160 to 180°C and maintained for 2 to 4 hours to obtain a prepolymer product;
[0066] (2) Cracking: The prepolymer product is transferred to a cracking reactor, and a cracking catalyst and a cracking solution are added. The temperature is set to 200-250°C, the pressure is maintained above -95KPa, and the reaction is further carried out for 6-12 hours. The distillate is collected in a collection tank;
[0067] Refining: refining and purifying the crude product in the collection tank to obtain glycolide product 2;
[0068] Polymerization: Transfer the product 2 obtained in step (2) into a polymerization device, add a catalyst, set the temperature to 130-210°C, and keep it warm for 2-5 hours to obtain product 3;
[0069] (3) transferring the product 3 obtained above to a twin-screw extruder, setting the screw speed to 10-40 rpm and the temperature to 200-250° C., and extruding and granulating the product using the twin-screw extruder;
[0070] (4) The pellets are transferred to a solid phase polymerization reaction device at a pressure of -99 KPa or above and at temperatures of 170°C for 2 to 8 h and 195°C for 4 to 12 h, respectively, to carry out solid phase polymerization to obtain product 33.
[0071] Example 3
[0072] A preparation process for preparing a degradable material and an intermediate, wherein the product 1 and the product 3 obtained in Example 1 and Example 2 are selected, and granulated according to a certain ratio to realize the production of a self-reinforced product, and the specific steps are as follows:
[0073] (1) adding product 1 obtained by polycondensation and viscosity enhancement and product 3 obtained by ring-opening polymerization into a twin-screw extruder at a certain ratio, setting the screw speed to 10-40 rpm and the temperature to 200-250° C., and extruding and granulating the products by the twin-screw extruder;
[0074] (2) The pellets are transferred to a solid phase polymerization reaction device at a pressure of -99 KPa or above and at temperatures of 170°C for 2 to 8 h and 195°C for 4 to 12 h, respectively, to carry out solid phase polymerization to obtain product 13.
[0075] The specific process of the five experimental groups using glycolic acid as raw material and polymerizing according to the above method is as follows:
[0076] Experimental Group 1
[0077] (1) Prepolymerization: Weigh 10 kg of glycolic acid and 10 L of xylene and add them to a prepolymerization reactor; set the heat transfer oil temperature to 138°C and the speed to 10 Hz, add catalyst nano zinc oxide, heat and stir, and keep the temperature in the kettle at 130°C for 2 hours; when the water content to be collected reaches 80% of the theoretical amount, set the heat transfer oil temperature to 165°C, and keep the temperature in the kettle at 160°C for 1.5 hours; when the water content to be collected reaches 90% of the theoretical amount, start vacuuming and gradually increase the pressure, maintain the pressure at -20 to -90 KPa, and adjust the temperature to 160 to 180°C and keep it for 2.5 hours;
[0078] (2) Polycondensation: The prepolymer product is transferred to a polycondensation reactor, the temperature is adjusted to 180-200°C, the pressure is maintained above -90KPa, and a condensation chain extender 1,3-dicyclohexylcarbodiimide is added, and the reaction is further carried out for 1 hour to obtain the product;
[0079] Viscosity enhancement: the polycondensation product prepared above was transferred to a viscosity enhancement reactor at a temperature of 180-200°C and a pressure of above -95KPa for 0.5h to obtain product 1;
[0080] (3) Production and granulation: Product 1 was transferred to a twin-screw extruder, the screw speed was set to 20 rpm, the temperature was set to 210°C / 235°C / 240°C / 245°C / 235°C, and the product was extruded and granulated using the twin-screw extruder;
[0081] (4) Solid-phase polymerization: The pellets were transferred to a solid-phase polymerization reaction device at a pressure of -99 KPa and a temperature of 170°C for 2 h and 195°C for 4 h, respectively, to carry out solid-phase polymerization to finally obtain product 11.
[0082] Experimental Group 2
[0083] (1) Prepolymerization: Weigh 10 kg of glycolic acid and 10 L of xylene and add them to the prepolymerization reactor; set the heat transfer oil temperature to 138°C and the speed to 15 Hz, add the catalyst nano zinc oxide, start heating and stirring, and keep the temperature in the kettle at 130°C for 2 hours; when the water content to be collected reaches 80% of the theoretical amount, set the heat transfer oil temperature to 165°C, and keep the temperature in the kettle at 160°C for 2 hours; when the water content to be collected reaches more than 90% of the theoretical amount, start the vacuum operation and gradually increase the pressure, maintain the pressure at -20 to -90 KPa, and adjust the temperature to 160 to 180°C and keep it for 3 hours;
[0084] (2) Polycondensation: The prepolymer product was transferred to a polycondensation reactor, the temperature was adjusted to 180-200°C, the pressure was maintained above -95KPa, and the condensation chain extender ADR-4370S was added, and the reaction was further carried out for 1.5 hours to obtain the product;
[0085] (3) Viscosity enhancement: the product of step (2) is further transferred to a viscosity enhancement reactor at a temperature of 180-200° C. and a pressure of above -98 KPa for 1 h to obtain product 1;
[0086] (4) Granulation: The product 1 is transferred to a twin-screw extruder, the screw speed is set to 20 rpm, the temperature is set to 225°C / 235°C / 240°C / 245°C / 235°C, and the product 1 is extruded and granulated by the twin-screw extruder;
[0087] (5) Solid-phase polymerization: The pellets were transferred to a solid-phase polymerization reaction apparatus at a pressure of -99 KPa and temperatures of 170°C for 3 h and 195°C for 5 h, respectively, to carry out solid-phase polymerization to obtain product 11.
[0088] Experimental Group 3
[0089] (1) Prepolymerization: Weigh 10 kg of glycolic acid and 10 L of xylene and add them to a prepolymerization reactor; set the heat transfer oil temperature to 138° C. and the speed to 15 Hz, start heating and stirring, and keep the temperature in the kettle at 130° C. for 2 h; when the water content to be collected reaches 80% of the theoretical amount, set the heat transfer oil temperature to 165° C., and keep the temperature in the kettle at 160° C. for 1 h; when the water content to be collected reaches more than 90% of the theoretical amount, start vacuuming and gradually increase the pressure, maintain the pressure at -20 to -90 KPa, and adjust the temperature to 160 to 180° C. and keep it for 2 h to obtain a prepolymer product;
[0090] (2) Cracking: The prepolymer product is transferred to a cracking device, and a cracking catalyst, antimony trioxide, and a cracking liquid, a mixture of dioctyl terephthalate and polyethylene glycol 1000, are added. The temperature is set at 220-250° C., the pressure is maintained above -95 KPa, and the reaction is further carried out for 8 hours. The distillate is collected in a collection tank;
[0091] Refining: The crude glycolide in the collection tank is transferred to the refining device for refining and purification to obtain the refined glycolide product 2;
[0092] Polymerization: Add the refined product 2 into the polymerization device, and add a mixed solution of stannous octoate and dodecanol as a catalyst, set the temperature to 130-210°C, and maintain the pressure above -95KPa for 3 hours to obtain product 3;
[0093] (3) Granulation: The product 3 was transferred to a twin-screw extruder, the screw speed was set to 20 rpm, the temperature was set to 225°C / 235°C / 240°C / 245°C / 235°C, and the product was extruded and granulated using the twin-screw extruder;
[0094] (4) Solid-phase polymerization: The pellets were transferred to a solid-phase polymerization reaction apparatus at a pressure of -99 KPa and temperatures of 170°C for 6 h and 195°C for 10 h, respectively, for further solid-phase polymerization to obtain product 33.
[0095] Experimental Group 4
[0096] (1) Prepolymerization: as in experimental group 3;
[0097] (2) Cracking: The prepolymer product is transferred to a cracking device, and a cracking catalyst, stannous octoate, and cracking liquids, dioctyl terephthalate and polyethylene glycol monomethyl ether, are added. The temperature is set at 220-250° C., the pressure is maintained above -96 KPa, and the reaction is further carried out for 10 hours. The distillate is collected in a collection tank;
[0098] Refining: The crude glycolide in the collection tank is transferred to the refining device for refining and purification to obtain the refined glycolide product 2;
[0099] Polymerization: Add the above product 2 into the polymerization device, and add a mixed solution of catalyst stannous octoate and dodecanol, set the temperature to 130-210°C, and maintain the pressure above -95KPa for 3.5 hours to obtain product 3.
[0100] The granulation and solid phase polymerization of steps (4) and (5), such as experimental group 3, finally obtain product 33.
[0101] Experimental Group 5
[0102] (1) Prepolymerization: as in experimental group 3;
[0103] (2) Cracking: The prepolymer product is transferred to a cracking device, and a cracking catalyst of zinc acetylacetonate and a cracking solution of butyl benzyl phthalate and polyethylene glycol 1000 are added, the temperature is set at 220-250° C., the pressure is maintained above -98 KPa, the reaction is further carried out for 10 hours, and the distillate is collected in a collection tank;
[0104] Refining: The crude glycolide in the collection tank is transferred to the refining device for refining and purification to obtain the refined glycolide product 2;
[0105] Polymerization: Add the above product 2 into the polymerization device, and add a mixture of catalyst stannous octoate and dodecanol, set the temperature to 130-210°C, and maintain the pressure above -95KPa for 4 hours to obtain product 3.
[0106] (3) Granulation and solid phase polymerization: As in Experimental Group 3, product 33 was finally obtained.
[0107] Experimental Group 6
[0108] (1) Direct polycondensation: Product 1 was obtained as in Experimental Group 2;
[0109] (2) Ring-opening polymerization: Product 3 was obtained as in Experimental Group 5;
[0110] (3) Granulation: Add product 1 and product 3 into a twin-screw extruder at a certain ratio at the same time, set the screw speed to 10-40 rpm, the temperature to 200-250° C., and extrude and granulate using the twin-screw extruder;
[0111] (4) Solid-phase polymerization: The pellets were transferred to a solid-phase polymerization reaction device at a pressure of -99 KPa or above and at temperatures of 170°C for 2 to 8 h and 195°C for 4 to 12 h, respectively, to carry out solid-phase polymerization to obtain product 13.
[0112]
[0113] By comparing experimental groups 1 to 2 with 3 to 5, it can be seen that the process device of the present invention can realize the production of PGA products with different gradients from low to high relative molecular weight;
[0114] It can also be seen from the table that the total yield of the direct polycondensation method of experimental groups 1 to 2 is much greater than that of experimental groups 3 to 5, that is, if a single production process is adopted, the cost of obtaining low molecular weight PGA by ring-opening polymerization is huge. However, the advantages of these two PGA preparation methods can be realized on the device of the present invention, and the optimal production of PGA cost can be achieved while meeting different application requirements, which is conducive to the market promotion and application of degradable material PGA.
[0115] In addition, by using the process of the present invention, the enhancement of direct polycondensation PGA by ring-opening polymerization PGA can be achieved through self-enhancement technology.
Claims
1. A production process for simultaneously preparing multiple molecular weight gradient degradable materials, characterized in that: The process consists of the following four steps: (1) Prepolymerization: weigh alkyd acid, dehydrating agent, and prepolymerization catalyst, add them into a reactor, heat and stir, and keep the temperature at 120-140°C for 1-3 hours; Wherein, the weight ratio of the prepolymerized catalyst to the raw material is: 0.5% wt; When the collected water content reaches 80% of the theoretical amount, the temperature in the kettle is raised to 150-170°C and maintained for 1-2 hours; When the collected water content reaches 90% of the theoretical amount, start the vacuum operation and gradually increase the pressure, maintain the pressure at -20~-90 KPa, and adjust the temperature at 160~180℃ for 2~4 hours to obtain the prepolymer product; (2) Polymerization: direct polycondensation to increase viscosity, or ring-opening polymerization to obtain polymer products; (3) Production and granulation: The polymer product prepared in step (2) is extruded and granulated using a twin-screw extruder to obtain pellets, with the screw speed set at 10-40 rpm and the extrusion temperature at 200-250°C; (4) solid phase polymerization: the pellets obtained in step (3) are subjected to solid phase polymerization, wherein the pressure is maintained above -99 KPa and the temperature is 170°C for 2 to 8 h and 195°C for 3 to 12 h, respectively, to finally obtain alkyd polymer products with various molecular weight gradients; The direct polycondensation and viscosity enhancement in step (2) of the process for preparing medium and low molecular weight biodegradable materials specifically comprises the following steps: S1, polycondensation: transfer the prepolymer product obtained in step (1) to a polycondensation reactor, adjust the temperature to 180-200°C and the pressure to above -90 KPa, add a condensation chain extender, and react for 1-2 h to obtain a polycondensation product; S2, viscosity increasing: transferring the polycondensation product prepared in step S1 to a viscosity increasing kettle, the temperature is 180-200°C, the pressure is maintained above -95KPa, and a viscosity increasing reaction is performed to obtain a polymer product; The ring-opening polymerization in step (2) of the process for preparing the high molecular weight biodegradable material specifically comprises the following steps: S1, cracking: the prepolymer product obtained in step (1) is transferred to a cracking reactor, and a cracking catalyst and a cracking solution are added, the temperature is set to 200-250°C, the pressure is maintained above -95 KPa, and the reaction is further carried out for 6-12 hours, and the distillate is collected in a collection tank; S2, refining: refining and purifying the crude product in the collecting tank of step S1 to obtain refined glycolide; S3, polymerization: the refined glycolide product obtained in step S2 is transferred into a polymerization device, and a polymerization catalyst is added, the temperature is set to 130-210° C., and the temperature is kept for 2-5 hours to obtain a polymer product; The system structure used in this production process is as follows: It comprises a prepolymerization device, wherein the outlet d of the prepolymerization device is respectively connected to the inlet a of the polycondensation device and the inlet a of the cracking device, and the outlet c of the prepolymerization device is connected to the inlet a of the heat exchanger 51; the outlet of the cracking device is connected to the inlet of the refining device 33, the outlet of the refining device 33 is connected to the inlet of the ring-opening polymerization device 34, the outlet of the ring-opening polymerization device 34 and the outlet of the polycondensation device are both connected to the inlet of the production granulation device; the outlet of the production granulation device is connected to the inlet of the solid-phase polymerization device 44; the outlet b of the heat exchanger 51 is connected to the inlet of the vacuum device, and the outlet c of the heat exchanger 51 is connected to the condensate storage tank 52; The outlet channel d of the prepolymerization device leading to the polycondensation device and the cracking device is provided with a three-way switch valve 6, which is respectively connected to the inlet of the polycondensation device and the inlet of the cracking device; The prepolymerization device includes a preheating tank 11, a prepolymerization kettle 12, and a solvent reflux tank 13; the inlet a of the preheating tank 11 is connected to the feed control system; the inlet b of the preheating tank 11 is connected to the inlet a of the prepolymerization kettle, and the inlet a and outlet b of the solvent reflux tank 13 are respectively connected to the outlet b and inlet c of the prepolymerization kettle 12, forming a reflux mode; The cracking device includes a cracking kettle 31 and a crude product collecting tank 32; the polycondensation device includes a polycondensation kettle 21 and a viscosity increasing kettle 22; the outlet c of the solvent reflux tank 13 in the cracking device is connected to the inlet of the heat exchanger 51; the outlet d of the prepolymerization kettle 12 is connected to the inlet a of the polycondensation kettle 21 and the inlet a of the cracking kettle 31 through a three-way switch valve 6; The above system also includes a high and low temperature control system, which is respectively connected to the prepolymerization device, the polycondensation device and the cracking device; The outlet b of the cracking kettle 31 is connected to the inlet of the heat exchanger 51, the outlet c of the cracking kettle 31 is connected to the inlet of the crude product collecting tank 32, and the outlet of the crude product collecting tank 32 is connected to the refining device 33; The outlet b of the polycondensation kettle 21 is connected to the inlet of the heat exchanger 51, the outlet c of the polycondensation kettle 21 is connected to the inlet of the viscosity increasing kettle 22, and the outlet of the viscosity increasing kettle 22 is connected to the inlet of the twin screw extruder 41; the twin screw extruder 41 is a part of the production granulation device; The production granulation device comprises a twin-screw extruder 41, a granulator 42, and a silo 43. The inlet of the twin-screw extruder 41 is respectively connected to the outlet of the viscosity increasing kettle 22 and the outlet of the ring-opening polymerization device 34, the outlet of the twin-screw extruder 41 is connected to the inlet of the granulator 42, the outlet of the granulator 42 is connected to the inlet of the silo 43, and the outlet of the silo 43 is connected to the inlet of the solid phase polymerization device 44; The vacuum device includes a cyclone separation tank 53, a buffer tank 54, and a vacuum pump 55. The inlet of the cyclone separation tank 53 is connected to the outlet b of the heat exchanger 51, the outlet of the cyclone separation tank 53 is connected to the inlet of the buffer tank 54, and the outlet of the buffer tank 54 is connected to the inlet of the vacuum pump 55.
2. The production process according to claim 1, characterized in that: The dehydrating agent described in (1) is xylene, and the prepolymerization catalyst is nano zinc oxide.
3. The production process according to claim 1, characterized in that: (2), the condensation chain extender of the direct polycondensation process is any one of 1,3-dicyclohexylcarbodiimide and ADR-4370S; The cracking catalyst of the ring-opening polymerization process is any one of antimony trioxide, stannous octoate, and zinc acetylacetonate; The cleavage solution is any one of a mixture of dioctyl terephthalate and polyethylene glycol 1000, a mixture of dioctyl terephthalate and polyethylene glycol monomethyl ether, and a mixture of butyl benzyl phthalate and polyethylene glycol 1000; The polymerization catalyst is a mixed solution of stannous octoate and dodecanol.